Hybrid Algorithm with Super Encryption of Medical Record Image Data - Khudzaifah, Muhammad; Qorny, Muhamad Wais Al; Sa’adati, Hawzah (Proceedings of the International Conference on Green Technology; Vol 8 No 1 (2017): Proceedings of the International Conference on Green TechnologyDO - 10.18860/icgt.v8i1.273, 2017)
In the technology information, security becomes very important to secure data. One of the most secret data and needs to be secured is medical record data in the form of an image. The method that can be used to secure it is a cryptographic algorithm. Thera are two cryptographic algorithm that can be used to secure medical record data that is symmetric and asymmetric. Symmetric algorithm fast in the process of encryption and decryption, but less secure in the key, while asymmetry slow in process of encryption and decryption, but safe with yhe key. To get an efficient result, the used hybrid algorithm, that is symmetric algorithm for process of encryption and decryption, while the key is secured with asymmetric algorithms. In this research, the symmetric algorithm uses super encryption (affine cipher and transformation), while the asymmetric algorithm uses RSA algorithm. The result obtained are the process of encryption and decryption need a short tme and the security of the key more increased.